2012
DOI: 10.1002/anie.201200069
|View full text |Cite
|
Sign up to set email alerts
|

Stereospecific Carbene Polymerization with Oxygenated Rh(diene) Species

Abstract: Breath‐taking activation: Stereoregular carbene polymerization proceeds via cationic [(allyl)RhIII–polymeryl]+ species. These are most efficiently generated by oxygenation of the [(diene)RhI] precatalysts, which involves an unusual rearrangement of 2‐rhodaoxetane intermediates. This discovery gives detailed insight in the reaction mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 44 publications
1
55
0
Order By: Relevance
“…In both cases, it is the change in the total charge of the complex that probably makes such transformations possible. The reactions shown in Scheme thus clearly prove the chemical non‐innocence of the cod ligands in the complexes presented herein 4hj…”
Section: Resultssupporting
confidence: 57%
“…In both cases, it is the change in the total charge of the complex that probably makes such transformations possible. The reactions shown in Scheme thus clearly prove the chemical non‐innocence of the cod ligands in the complexes presented herein 4hj…”
Section: Resultssupporting
confidence: 57%
“…266 The reaction proceeds via a migratory insertion mechanism (Scheme 55) 266 and no or little chain transfer seems to occur. [275][276][277][278] Most recently, detailed mechanistic studies revealed that the active species responsible for this polymerisation is a Rh III (allyl)(alkyl) species (Fig. 7) that can be formed by modifications of rather simple Rh I (diene) precursors (e.g.…”
Section: Scheme 49 Migratory Insertion Of Carbenesmentioning
confidence: 99%
“…1 In the past 100 years, generations of polymer chemists have spent considerable efforts to develop different kinds of polymerization methods based on the corresponding organic reactions, resulting in prosperous polymer science with abundant synthetic polymer materials in the form of plastics, fibers, rubbers, etc., which have played important roles in human life. [2][3][4][5][6][7][8][9][10][11] For example, polyesterification and polyamidation are based on the corresponding esterification and amidation reactions, resulting in significant polyesters and polyamides, e.g., polyethylene terephthalate (PET) and nylon. [12][13][14] A series of coupling polymerizations are based on the corresponding Stille-, Suzuki-, Kumada-coupling reactions, etc.…”
Section: Introductionmentioning
confidence: 99%